PENGARUH MODEL PROBLEM BASED INSTRUCTION (PBI) TERHADAP HASIL BELAJAR FISIKA PESERTA DIDIK KELAS XI SMAN 1 MALIGANO - Halmuniati, Halmuniati; Sari, Rahma; Isa, La; Madi, Nasir (Universitas Tadulako, 2022)
This research was conducted with the aim of knowing the effect of the Problem Based Instruction model on the physics learning outcomes of class XI students of SMA Negeri 1 Maligano. This study used a quasi-experimental design where there were pre-test and post-test in the experimental class and the control class. The population used in this study were all students of class XI SMA Negeri 1 Maligano, the sample was determined by purposive sampling technique, namely by selecting two classes with almost the same or homogeneous values, class XI IPA 1 as the experimental class and class XI IPA 2 as the control class. The analysis prerequisite test includes the normality test, homogeneity test, and hypothesis testing to determine the learning outcomes of the experimental class and control class. The results showed that there was an effect of the Problem Based Instruction model on learning outcomes as seen from the difference in learning outcomes after treatment in the experimental class and control class, t_count < t_table or 2.6779 > 2.028094. Thus, the cognitive learning outcomes of students who were given the Problem Based Instruction model had a significant effect.